Contemporary macroeconomics / edited by Debraj Ray, Abhirup Sarkar and Amitava Bose - Ray, Debraj .(ed.) (New Delhi, 2002)
This collection of essays provides an examination of the essential aspects of modern macroeconomics that is ideally suited for researchers and graduate students in the field.
Keywords: Macro economics